ORAL ANTICOAGULANTS IN PATIENTS WITH DIFFERENT FORMS OF PULMONARY ARTERIAL HYPERTENSION, ASPECTS OF THE PROBLEM - S. Ye. Gratsianskaya; T. V. Martynyuk; S. N. Nakonechnikov; I. Ye. Chazova (Евразийский Кардиологический Журнал, 2017)
The use of direct oral anticoagulants in patients with pulmonary arterial hypertension (PAH) has remained a controversial issue for a decade. Despite the lack of solid evidence from well-controlled prospective trials, anticoagulation has been recommended for patients with idiopathic pulmonary arterial hypertension (IPAH), but it is unclear whether this recommendation should be extrapolated to patients with other forms of PAH. In this review, we discuss the current opportunities and problematic aspects of oral anticoagulation therapy in different forms of PAH, the influence on disease course and prognosis..